Analisis Penerapan Full Costing Dalam Penentuan Harga Pokok Produksi ( HPP) Pada Usaha Mikro Kecil Dan Menengah (Studi Kasus Pada Usaha Jahit Pertiwi Di Pasar Tingkat Maumere) - Korina, Theovila; Dince, Maria Nona; Lamawitak, Paulus Libu (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2025)
This study aimed to analyze the application of the full costing method in determining the cost of production at Pertiwi Tailoring Bussiness In Pasar Tingkat Maumere. The research employed a descriptive method with a quantitative approach, in which data were collacted through interviews, observations, and documentation. The result showed that the calculation of cost of production carried out so far was still simple because it only included raw material costs and direct labor, without taking into account factory overhead costs, both fixed and variable. This resulted in a selling price determination that often did not reflect the actual production cost. By applying the full costing method, the calculation of the cost of production became more accurate since it included raw materials, direct labor, and all factory overhead costs. The appication of this method provided more complete and accurate cost information, so it could serve as a basis for setting appropriate selling prices, maintaining competitiveness, and ensuring that the business earned fair and sustainable profits.